Evaluasi Standar Nasional Perpustakaan (SNP) Sekolah di Sekolah Menengah Pertama (SMP) Se-Kecamatan Pattallassang Kab. Gowa - Marni; Trysnawati, Ayu (UPT Perpustakaan UIN Alauddin Makassar, 2025)
This study aims to analyze the achievement of library facilities and infrastructure at SMP 1 Pattallassang and SMP 2 Pattallassang based on the National Library Standards (SNP) for Schools Number 11 of 2017. The research uses a descriptive qualitative method. Data were collected through observation, interviews, and documentation, with five librarians as data sources. The analysis was conducted in three stages: data reduction, data presentation, and conclusion drawing. The results show that the achievement of library facilities and infrastructure standards in both schools is quite good, although some aspects are still unmet, particularly regarding the library's location, which remains integrated with the school building. Available facilities include work desks and chairs, reading tables and chairs, bookshelves, catalog cabinets, magazine racks, circulation desks, and computer equipment. Librarians strive to meet the standards by providing the necessary facilities. SMP 2 Pattallassang implements a floor-seating method for visitors, while SMP 1 Pattallassang provides two models of reading tables: tables that can be used as classrooms and tables with partitions to enhance visitor comfort. In conclusion, school libraries have met most of the standards, although improvements are still needed in terms of location and certain infrastructure aspect.